The effect on feedlot performance and digestibility of whole crop barley and oats fed as silage and hay in lambs - Tatli, P; Cerci, IH (Sciendo, 2001)
This study was conducted to determine qualities of silages and effects on food intake, body weight gain, feed:gain ratio and nutrient digestibility in lambs of whole crop barley and oats las silage or hay) harvested at the milk stage. Twenty four 8 month old Akkaraman male lambs, averaging 26,02 kg were assigned randomly to four groups. Lambs received one of two forage sources (barley or oats) conserved in one of two ways (silage or hay) during the experiment, The Ist diet included barley silage; 2nd diet included barley hay; the 3rd diet included oat silage while the 4th diet included oat hay. Dry matter (DM) levels were 31, 76; 84,86; 30,95; 86,62 % for each group respectively. The pH, NH3-N and lactic acid levels of the silages were determined as 4.9; 5.20: 0.52; 0.55 % and 2.54; 2.00 in DM respectively. Dry matter intakes (DMI) of the lambs were 471; 981; 434 and 1007 g in each group, respectively (P <0.01). Body weight gains (BWG) were found to be 93.2; 84.7; 81.9, 85,7 g/day in each group respectively. Feed: gain ratios were determined as 5.05; 11.58; 5.33; 11.74 g DMI/g BWG for each group respectively Dry matter, crude protein and crude cellulose digestibility were determined as 64.96; 54.53; 63.62; 52.09 %; 63.44; 46.78; 61.98; 44.52 %; 59.15; 47.42; 61.45; 49.05 % for each group, respectively (P <0.05).
Keywords: barley; digestibility; feedlot performance; hay; oat; silage